Urgensi Psikologi Islam Dalam Pendidikan Islam - Mubarak Mubarak (Faculty of Ushuluddin and Humanities, 2017)
This paper examines the urgency of Islamic Psychology in Islamic Education. Education and psychology cannot be separated, both have a very close relationship. Education is a long process to actualize all the potential of human self so that the potential of humanity to be actual. In terms of Islamic education is needed is Islamic Psychology, because humans have the potential of noble, namely fitrah and spirit that is not touchable in general psychology (West). Islamic education should have a psychological foundation that is insightful to Islam, in this case with a guide to the Qur'an and Hadith as its source, so that the end of the goal of Islamic education can be realized and create a plenary human (insan kamil).Islamic education psychology devotes attention to the behavior or behavior of those who engage in learning and teaching activities or those directly involved in the learning process. Islamic education psychology has two objects, namely: First, learners, ie individuals (individuals) who are learning, including approaches, strategies, influencing factors and achievements achieved. Secondly, teachers (educators), those who are obliged or undertake teaching responsibilities, including methods, models, strategies, and others related to the activity of presenting Islamic education. Islamic education based on Islamic Psychology will produce human beings who have a potential base that is a qualified potential of physical, spiritual, and fitrah or better known as jismiah, nafsiah and ruhaniah.